Oceania : the native cultures of Australia and the Pacific Islands - Oliver, Douglas L. (University of Hawaii Press, 1989)
Social life and customs; Part one, hunting and food gathering; social relations; habitation; dwellings; boats; canoes; warfare; killing; weapons; exchange; barter; trade routes; trade ceremonies; corroborees; relationships reproduction; life cycle; Part two, Murngin of northeast Arnhem Land, myths; kinship system; households; communities; patriclans, matriclans; Yirrkalla [sic] clan designs; kin classification.